Invasive lobular carcinoma: integrated multi-omics analysis reveals silencing of Argininosuccinate synthase and upregulation of nucleotide biosynthesis in tamoxifen resistance - Annapurna Gupta; Fouad Choueiry; Jesse Reardon; Nikhil Pramod; Anagh Kulkarni; Eswar Shankar; Steven T. Sizemore; Daniel G. Stover; Jiangjiang Zhu; Bhuvaneswari Ramaswamy; Sarmila Majumder (Cell Death and Disease)
Abstract Invasive Lobular Carcinoma (ILC), a distinct subtype of breast cancer, is hallmarked by E-Cadherin loss, slow proliferation, and strong hormone receptor positivity. ILC faces significant challenges in clinical management due to advanced stage at diagnosis, late recurrence, and development of resistance to endocrine therapy - a cornerstone of ILC treatment. To elucidate the mechanisms underlying endocrine resistance in ILC, ILC cell lines (MDA-MB-134-VI, SUM44PE) were generated to be resistant to tamoxifen, a selective estrogen receptor modulator. The tamoxifen-resistant (TAMR) cells exhibit a 2-fold increase in tamoxifen IC50 relative to parental cells. Metabolomics and RNA-sequencing revealed deregulation of alanine, aspartate, and glutamate metabolism, purine metabolism, and arginine and proline metabolism in TAMR cells. Among the fifteen commonly dysregulated genes in these pathways, low argininosuccinate synthase (ASS1) expression was identified in the TAMR cells and was significantly correlated with poor outcome in ILC patients, specifically in the context of endocrine therapy. Our study reveals methylation-mediated silencing of ASS1 in TAMR cells as a likely mechanism of downregulation. Demethylation restored ASS1 expression and correspondingly reduced tamoxifen IC50 toward parental levels. Nucleic acid biosynthesis is augmented in TAMR cells, evidenced by an increase in nucleotide intermediates. Both TAMR cell lines demonstrated increased expression of several nucleic acid biosynthesis enzymes, including PAICS, PRPS1, ADSS2, CAD, and DHODH. Furthermore, CAD, the key multifunctional protein of the de novo pyrimidine biosynthesis pathway, is differentially activated in TAMR cells. Treating TAMR cells with Decitabine, a demethylating agent, or Farudodstat, a pyrimidine biosynthesis inhibitor, markedly augmented the efficacy of tamoxifen. Collectively, our study unveils ASS1 downregulation as a novel mechanism underlying acquired tamoxifen resistance in ILC and establishes a metabolic link between ASS1 and nucleic acid biosynthesis. Restoring ASS1 expression or inhibiting pyrimidine biosynthesis reinstated tamoxifen sensitivity. ASS1 could be a potential biomarker and therapeutic target in tamoxifen-resistant ILC patients, warranting further investigation.